A Critical Edition and Annotated Translation of the Late Nineteenth and Early Twentieth Century Treatise: Tārik Zamǝdra Gondar (The History of the Land of Gondar) - Beyene, Sisay Sahile (Aethiopica, 2022)
Dissertation Abstract